Penerapan Semantik dalam Pembelajaran Bahasa Indonesia SMA Swasta Sinar Pancasila - Anggelina T. Pires; Joel Tasman; Octa Mendonca; Desantri Mali; Mersiana L. Klau; Emeliana Tai (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The purpose of this writing is to find out the extent of the application of semantics in Indonesian language learning at Sinar Pancasila Private High School. Apart from that, this research also provides a specific picture of the problem of semantic learning in schools. Data is taken from sentences delivered by a teacher who are interested in semantics. Data sources were taken from the semantics of books written by experts and interviews with fellow Indonesian language teachers at Sinar Pancasila Private High School. The research results show that there are several semantic meanings used in Indonesian language learning, namely, affective meaning, denotative meaning, descriptive meaning, emotive meaning, figurative meaning. Apart from that, several efforts were also found that could overcome semantic learning problems in schools.